2012
DOI: 10.1039/c2mb25115a
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic analysis of polar metabolites in lipoprotein fractions identifies lipoprotein-specific metabolic profiles and their association with insulin resistance

Abstract: While the molecular lipid composition of lipoproteins has been investigated in detail, little is known about associations of small polar metabolites with specific lipoproteins. The aim of the present study was to investigate the profiles of polar metabolites in different lipoprotein fractions, i.e., very-low-density lipoprotein (VLDL), intermediate-density lipoprotein (IDL), low-density lipoprotein (LDL) and two sub-fractions of the high-density lipoprotein (HDL). The VLDL, IDL, LDL, HDL(2), and HDL(3) fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Other reported markers of insulin resistance or T2D primarily from cross-sectional studies include increased fasting blood or urine stearoyl-CoA desaturase-derived fatty acids, glucose derivatives and gluconeogenic precursors, bile acids or derivatives, cystine-cysteine (e.g., [5], [7], [8], [15], [16], [69], [70]), and decreased glycine, glutamine, L-GPC, and arachidonic acid (e.g., [5], [7][9], [13], [15], [16], [71]). Under conditions of a glucose challenge, individuals with insulin resistance had a blunted response in terms of blood lactate, bile acid or TCA-associated organic acid increases and glycerol and β-hydroxybutyrate decreases [17], [20]).…”
Section: Discussionmentioning
confidence: 99%
“…Other reported markers of insulin resistance or T2D primarily from cross-sectional studies include increased fasting blood or urine stearoyl-CoA desaturase-derived fatty acids, glucose derivatives and gluconeogenic precursors, bile acids or derivatives, cystine-cysteine (e.g., [5], [7], [8], [15], [16], [69], [70]), and decreased glycine, glutamine, L-GPC, and arachidonic acid (e.g., [5], [7][9], [13], [15], [16], [71]). Under conditions of a glucose challenge, individuals with insulin resistance had a blunted response in terms of blood lactate, bile acid or TCA-associated organic acid increases and glycerol and β-hydroxybutyrate decreases [17], [20]).…”
Section: Discussionmentioning
confidence: 99%
“…For example, our results in the negative ion mode indicated that heneicosanoic acid ( m / z 325) was presented in standard chow, and it was incorporated by liver and liver mitochondria in control mice (Figure S1). Although the role of this fatty acid has still not been described in mitochondria, it is known that it participates as an energy source and it is also important to the membrane integrity/stability of several cell types . Similarly, linoleic acid ( m / z 279) was incorporated by the liver of mice in the control group (Figure S1).…”
Section: Discussionmentioning
confidence: 96%
“…Although the role of this fatty acid has still not been described in mitochondria, it is known that it participates as an energy source and it is also important to the membrane integrity/stability of several cell types. [34][35][36] Similarly, linoleic acid (m/z 279) was incorporated by the liver of mice in the control group ( Figure S1). This compound is an essential fatty acid, and it is known to keep the water permeability barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomic studies in metabolic diseases 31 have been used to identify novel biomarkers that associate with IR 23,32,33 and predict T2DM. [34][35][36] The three metabolites used in the test have a number of potential roles in metabolic pathways relevant to insulin action, insulin secretion, or β-cell function.…”
Section: Metabolite Biomarkers Of Insulin Resistancementioning
confidence: 99%